ANTIMUTAGENIC ACTIVITY OF ALCOHOLIC EXTRACTS OF MEDICINAL HERBS MENTHA PIPERÍTA L. AND THYMUS VULGARIS L. FAMILY LAMIACEAE (Eurasian Journal of Ecology, 2022)
The global pollution of environment urges the screening of effective natural protectors for the correc-tion of toxic and genotoxic action of xenobiotics. Medicinal herbs contain a complex of biologically ac-tive compounds that are the potential sources of such a protective agent. In current study the mutagenic and antimutagenic activity of alcoholic extracts of peppermint (Mentha piperita L.) and thyme (Thymus vulgaris L.), family Lamiaceae, was studied using the chromosome aberration assay (metaphase cytoge-netics) in barley. The ability of extracts to significantly reduces methyl methanesulfonate-induced mu-tagenesis under preliminary or subsequent tinctures exposure was established (p